The effect of carbohydrate feeding during cycling on run performance within a simulated Olympic-distance triathlon - McGawley, K.; Shannon, O. (Journal of Science and Medicine in Sport, 2010)
The purpose of the present study was to examine the effects of carbohydrate ingestion during the cycle leg of a simulated Olympic-distance triathlon (1500-m swim, 40-km cycle, 10-km run) on subsequent running performance. Methods: Five well-trained triathletes (4 male, 1 female) volunteered to participate (mean ± SD age: 23.6 ± 4.2 y, body mass: 63.0 ± 7.6 kg and VO2max: 64.0 ± 9.0 ml kg-1 min-1). Participants attended three separate testing sessions separated by at least five days. The first session involved a 1500-m swim time-trial (STT) followed approximately 30 min later by a graded cycle test to exhaustion for the evaluation of maximal aerobic power (MAP). The two subsequent sessions required participants to complete a simulated Olympic-distance triathlon involving a 1500-m pool swim to within 5% of the STT, a 40-km stationary cycle at 75% of MAP and a 10-km running time trial. Participants randomly consumed either a 14.4% carbohydrate drink containing 1.2 g min-1 of glucose and 0.6 g min-1 of fructose (CHO) or a fruit squash placebo (PLA) throughout the cycle leg of the triathlon. Fingertip blood samples were collected after every 5 km of the cycle leg and at the end of the run and were subsequently analysed for blood glucose (GLU) and lactate (LAC) concentrations. Rating of perceived exertion (RPE) and perceived stomach upset (PSU) were also measured after each 5-km cycle period and at the end of the run. Heart rate (HR) was measured throughout the cycle leg only. Results and conclusion: The 10-km run time was 4.2% faster following CHO (38 min 08 s ± 2 min 46 s) compared with PLA (39 min 44 s ± 3 min 13 s; P < 0.05). The improved run time was associated with increased GLU and LAC concentrations in the CHO compared with the PLA trial (P < 0.05), no difference in HR or PSU between trials (P > 0.05) and significantly lower RPE scores in the CHO compared with the PLA trial (P < 0.05). These results show that a 10-km run at the end of an Olympic-distance triathlon may be significantly improved following ingestion of a 14.4% glucose-fructose beverage at a rate of 1.8 g min-1 compared with a fruit squash placebo, with no additional gastro-intestinal stress. This improvement in run performance in the CHO trial may be due to muscle and liver glycogen sparing during the cycle leg, which increased carbohydrate metabolism in the latter stages of the triathlon.